Food budget allocation efficiency: A missing component to help identify robust nutrition policies, with application to Rwanda - Marivoet, Wim (International Food Policy Research Institute, 2022)
This paper presents two interrelated innovations to help identify diet-related nutrition policies. The first involves the development of a food budget allocation efficiency measure to quantify suboptimal food preferences, which is one key explanation of poor diets in addition to unaffordability. The second relates to the application of stochastic dominance to a portfolio of dietrelated nutrition policies, defined by various levels of allocation efficiency and affordability. As no full specification is needed, the latter technique is particularly useful when lacking normative guidelines regarding the relative importance of nutrient deficiencies within one-dimensional diet quality measures as well as the exact content of culture-sensitive diets. The analytical innovations are illustrated using a 2013/14 household consumption survey of Rwanda, a country characterized by both high calorie and micronutrient deficiencies. The origins of these poor nutritional outcomes can be traced back to various combinations and levels of affordability and allocation efficiency constraints. By only excluding the most inequality averse diet quality pecification, which may help to account for measurement error, a robust set of policy recommendations can be formulated for two thirds of all observations, most of which should focus on awareness raising activities.